Genetic divergence among white-type acai palm accessions based on morpho-agronomic characters - Sousa, Angela Maria de; Oliveira, Maria do Socorro Padilha de; Farias Neto, João Tomé de (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to quantify the genetic divergence among accessions of white-type acai palm, through morpho-agronomic characters. The accessions belong to the active acai palm germplasm bank of Embrapa Amazônia Oriental. Thirteen characters were evaluated in 26 accessions, originated from six municipalities in the state of Pará, Brazil. The data were subjected to deviance and multivariate analyses, based on the average Euclidean distance, and were grouped by Tocher’s method and the unweighted pair group method with arithmetic mean (UPGMA). The accessions differed for eight characters. The distances among accessions ranged from 0.64 to 2.62, with an average of 1.36, and four groups were formed by Tocher’s method and two by the UPGMA. Seven major components explained 88.03% of the variation, whose graphic dispersion showed the tendency of forming four groups. The characters weight of 100 fruits, number of rachillae per bunch, and fruit yield per bunch contributed the most to the divergence, and the accessions from the municipalities of Breves, Curralinho, and Limoeiro do Ajuru were the most divergent. Therefore, the accessions of white acai palm show strong divergence and variability, which favor the selection of desirable individuals.